Pengaruh Kualitas Layanan, Brand Image dan Terpaan Social Media Marketing Terhadap Loyalitas Pelanggan Layanan Subscription Video-on-Demand Netflix - Veriska, Veriska; Pradekso, Tandiyo (Interaksi Online, 2024)
This research examines the impact of service quality, brand image, and social media exposure on customer loyalty in the context of Subscription Video on Demand (SVoD) services, with a specific focus on Netflix in Indonesia. Despite being a pioneer in the Indonesian SVoD market, Netflix experienced a decline in market share in 2022. The study aims to understand the factors influencing customer loyalty, employing the Expectancy Disconfirmation Theory, Customer-Based Brand Equity, and Advertising Exposure Theory, along with Expectancy Confirmation Theory. The sampling technique utilized non-probability sampling, with a sample size of 100 respondents comprising Generation Z and millennials residing in the Jakarta-Bogor-DepokTangerang-Bekasi (Jabodetabek) area. Regression analysis results indicate that service quality has a significance value of 0.000, with a positive coefficient of 0.144, and brand image has a significance value of 0.000, with a positive coefficient of 0.208 which show that there’s an influence of service quality and brand image on Netflix’s customer loyalty. Meanwhile, social media exposure does not show a significant impact on Netflix’s customer loyalty. These findings suggest that prioritizing and enhancing service quality and brand image can be strategic focuses for companies aiming to strengthen customer loyalty in the SVoD industry.